Laporan Penelitian Potensi Desa Inovasi di Kabupaten Pemalang - Puji Dwi Darmoko (Madaniyah, 2015)
The emergence of various issues such as global warming and inequality of rural and urban communities in terms of development and lifestyle make problems, even lead to disharmony of life that leads to the threat of national unity. Therefore it is necessary to thoroughly study the optimization of the potential of natural resources and human resources in the village. One of them is the village innovation program, a village that is able to utilize village resources in a new way based on science and technology and local wisdom for the welfare of the community, the progress of the village and the improvement of the standard of living of the community by involving all elements of the village. This study seeks to uncover various potentials in 34 villages in 7 sub-districts in the Pemalang District, with an analysis of Talcott Parson's structural functionalism approach with four functional frameworks, namely adapttion, integration, goal attainment, and lithency pattern maintenance). The approach resulted in 10 pilot villages Innovation Village.